Raft Foundation Analysis Using Matlab And Crystal Ball Program - Al-Alaby, Aulia Rahman (2014)
Solo city is a city that is located in central of java, as the result solo city becomes trade center in java island. Furthermore, the position of the town as a solo 3- way intersection of the east of the area east of Java, north of the area and the coast road west of the city of Yogyakarta. This opportunity is needed to make any investment such as hotel. Hotel Anugerah Palace is built on area of 1100 m2, consists of 9 floors and 1 Basement. The project is scheduled to finish in June 2013. Due to the construction of this hotel, it is located in center of the city and make the access is easy. This final project analyzes raft foundation using probability and structural design. There are 2 program analysis, MATLAB and Crystal Ball which total load is 11602456,667 kg and width of area 1026,930 m2. CPT-Test data is analyzed using statistics method to obtain frequency of distribution and statistics parameter such as Mean, Standard Deviation, coefficient of variation. The value of qc as variable to calculate raft foundation and results the value of Chi-Square ( ) that make 4 type of distribution, normal distribution, gamma, beta and log-normal. The result of MATLAB program analysis can be seen that for qc at point 1 (S1), 2 (S2), 3 (S3) and 4 (S4) the distribution value that represent is Normal and at all point that combined the distribution value that represent is Normal. The result of analysis program of MATLAB 7.0 can be seen that the result for best fit distribution at all point and combined all point < (0.05 ; 3) (11,071). The result of Crystal Ball program analysis by level of confidence 90% - 95% value of SF is 1,5 or more than it and it is used for structural design for raft foundation. The result of structural design of raft foundation which the thickness of mat is 1,26 m. The determination of reinforcement for coordinate x and y axis, for area at sphere is used D25-140 and for area at pillar is used D25-140 as main bar and D25-190 as prop bar.